2020
DOI: 10.1111/ffe.13189
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of stress singularity for the circumferential V‐shape corner front of a three‐dimensional diamond‐like defect

Abstract: Three‐dimensional diamond‐like defects with circumferential V‐shape corner fronts are often contained in engineering materials. In this paper, generalized stress intensity factors are calculated for this type of defect using a modified advanced finite element method. A super corner front element model in the global coordinates is established to capture the stress singularities along the circumferential corner front. Three‐dimensional numerical series eigen‐solutions in the element have been transformed from as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…In recent years, Chen and Ping 43–45 have developed a 2D hybrid crack‐tip singular element by using the numerical eigensolution of the singular stress field on the basis of the one‐dimensional (1D) finite element eigenanalysis method, which avoids difficulty in accessing exact analytical solutions for asymptotic displacement and stress fields. Ping et al 46,47 and Zhang et al 48 extended this singular element to three‐dimensional (3D) fracture mechanics problems. The singular stress field characteristics of complex defects such as V‐shaped notch, hole corner, multiphase material interface edge, inclusion corner, and interface crack are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Chen and Ping 43–45 have developed a 2D hybrid crack‐tip singular element by using the numerical eigensolution of the singular stress field on the basis of the one‐dimensional (1D) finite element eigenanalysis method, which avoids difficulty in accessing exact analytical solutions for asymptotic displacement and stress fields. Ping et al 46,47 and Zhang et al 48 extended this singular element to three‐dimensional (3D) fracture mechanics problems. The singular stress field characteristics of complex defects such as V‐shaped notch, hole corner, multiphase material interface edge, inclusion corner, and interface crack are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Through experimental methods, it is found that the inclusion size, location, chemical composition, and geometry have great influences on the drawing production and its applications 5 . Besides, the lifetime of wire is controlled by local singular stresses 6 and crack initiations 7 at the vicinity of inclusions. Previous researches have shown that the size and hardness of inclusions have a certain promotion effect on the generation of cracks and fractures of wire, 8,9 and the effect is more obvious especially in the larger sized inclusions 10 .…”
Section: Introductionmentioning
confidence: 99%